Intelligent systems in cybernetics and automation theory proceedings of the 4th Computer Science On-line Conference 2015 (CSOC2015), Vol 2: intelligent systems in cybernetics and automation theory - Silhavy, Radek (Springer International Publishing, 2015)
This volume is based on the research papers presented in the 4th Computer Science On-line Conference. The volume Intelligent Systems in Cybernetics and Automation Control Theory presents new approaches and methods to real-world problems, and in particular, exploratory research that describes novel approaches in the field of cybernetics and automation control theory. Particular emphasis is laid on modern trends in selected fields of interest. New algorithms or methods in a variety of fields are also presented. The Computer Science On-line Conference (CSOC2015) is intended to provide an international forum for discussions on the latest high-quality research results in all areas related to Computer Science. The addressed topics are the theoretical aspects and applications of Computer Science, Artificial Intelligences, Cybernetics, Automation Control Theory and Software Engineering.